2018
DOI: 10.2319/120417-829.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone and functional appliance on mandibular growth in an adolescent rat model

Abstract: The FA as well as GH+FA stimulated mandibular growth in adolescent rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…The use of a growth hormone in growing rats in combination with functional appliances results in condylar growth. The same results, but significantly less growth, were reported with the application of functional appliances without administering a growth hormone according to Wang et al [ 21 ]. There is also a correlation between the amount of mandibular advancement and the growth of the condyle.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The use of a growth hormone in growing rats in combination with functional appliances results in condylar growth. The same results, but significantly less growth, were reported with the application of functional appliances without administering a growth hormone according to Wang et al [ 21 ]. There is also a correlation between the amount of mandibular advancement and the growth of the condyle.…”
Section: Resultssupporting
confidence: 74%
“…Six studies used randomization methods when allocating animals into experimental and control groups [ 8 , 16 , 17 , 21 , 22 , 23 ], although they did not specify the method used. None noted any blinding of the experimental procedure, as this was not feasible with live animals wearing appliances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…through the digestive system. Moreover, as the KYNA was administrated in drinking water, all rats received the same feed and the potential impact of feed texture on mandible morphology and growth was reduced to minimum [46]. It is well known that KYNA given intra-gastrically is absorbed from the gut, distributed to internal organs and tissues, and finally excreted in the urine [35], without permanently elevating serum KYNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…According to Davidopoulou and Chatzigianni (2017) after the administration of growth hormone, facial convexity decreased, while the mandibular length and posterior facial height were both increased in children with a reduced somatic growth due to a different etiology (Choi et al, 2017). In addition, Wang et al (2018) reported that functional appliance treatment in combination with growth hormone administration stimulated mandibular growth in adolescent rats. Given these findings, there is a possibility that the growth hormone treatment or the combination of growth hormone treatment and functional therapy might have enhanced the mandibular growth in this case.…”
Section: Discussionmentioning
confidence: 99%